1984
DOI: 10.1056/nejm198402233100802
|View full text |Cite
|
Sign up to set email alerts
|

The “On–Off” Phenomenon in Parkinson’s Disease

Abstract: To determine whether the oscillating clinical response to levodopa in Parkinson's disease (the "on-off" phenomenon) reflects fluctuations in absorption and transport of the drug, we investigated this phenomenon in nine patients with an oscillating motor state. We studied the response to continuous infusion of levodopa and the effects of meals on the plasma levodopa concentrations and on the clinical response during oral and intravenous administration of the drug. Meals reduced peak plasma levodopa concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 497 publications
(82 citation statements)
references
References 18 publications
2
77
0
Order By: Relevance
“…The change in plasma levodopa concentration with domperidone was unrelated to the Ratio Ratio dose -dp +dp -dp:+dp -dp +dp -dp:+dp Nutt et al (1984) have confirmed and extended previous observations that when levodopa is given with food, there is delayed absorption and a lower peak plasma levodopa concentration that when levodopa is given alone. Likewise, high gastric acidity (RiveraCalimlim et al, 1970) and anticholinergic drugs (Fermaglich & O'Doherty, 1972;Morgan et al, 1975) will delay gastric emptying.…”
Section: Plasma Levodopa Concentrationsupporting
confidence: 76%
“…The change in plasma levodopa concentration with domperidone was unrelated to the Ratio Ratio dose -dp +dp -dp:+dp -dp +dp -dp:+dp Nutt et al (1984) have confirmed and extended previous observations that when levodopa is given with food, there is delayed absorption and a lower peak plasma levodopa concentration that when levodopa is given alone. Likewise, high gastric acidity (RiveraCalimlim et al, 1970) and anticholinergic drugs (Fermaglich & O'Doherty, 1972;Morgan et al, 1975) will delay gastric emptying.…”
Section: Plasma Levodopa Concentrationsupporting
confidence: 76%
“…LCIG is a very effective treatment modality administered into the proximal jejunum through a PEG tube, where levodopa is absorbed, thus bypassing the stomach and avoiding the risk of levodopa concentration fluctuations associated with erratic or irregular gastric emptying [20]. …”
Section: Discussionmentioning
confidence: 99%
“…Levodopa (L-dopa) is the most effective pharmacological agent for pd and remains the primary treatment for symptomatic patients. However, its long-term use is limited by motor complications and drug-induced dyskinesia (Nutt et al, 1984). Unfortunately, the majority of drugs for treating pd, particularly L-dopa, provide pulse stimulation of dopamine release rather than continuous stimulation.…”
Section: Contextmentioning
confidence: 99%
“…In later stages of the disease, the fluctuations become less deterministic and totally unpredictable eventually (on-off phenomenon) (Nutt et al, 1984).…”
Section: Contextmentioning
confidence: 99%